ATMPH 2020
DOI: 10.36295/asro.2020.231439
|View full text |Cite
|
Sign up to set email alerts
|

Detection and comparison of Sapovirus, rotavirus and norovirus among infants and young children with acute gastroenteritis

Abstract: Background: Acute gastroenteritis (AGE) remains a global public health problem. Rotavirus (RV), norovirus (NoV) and Sapovirus (SV) are recognized as an important causes of AGE among children worldwide. However, there is no information about prevalence of Sapovirus infection in Iraq. Objective: To assess the frequency of SV, RV and NoV in children with AGE, also to determine the risk factors associated with the disease. Methods: A cross section study was carried out for 93 children under the age of five years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The current study showed that there was no significant association between viral infection and sex, age, residency, mother education level, type of feeding and source of water that used to prepare milk, as shown in Table (2). This results consistence with [22], who reported that there was no significant association between RV infection and sex, mother education and water sources but a significant association was found between RV positivity and age. In addition, another study reported that no sex preference to acquired viral infection but RV-Ag was detected more in children less than 2 years of age [21].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The current study showed that there was no significant association between viral infection and sex, age, residency, mother education level, type of feeding and source of water that used to prepare milk, as shown in Table (2). This results consistence with [22], who reported that there was no significant association between RV infection and sex, mother education and water sources but a significant association was found between RV positivity and age. In addition, another study reported that no sex preference to acquired viral infection but RV-Ag was detected more in children less than 2 years of age [21].…”
Section: Discussionsupporting
confidence: 71%
“…A study carried by Abdulazeez et al, (2002) demonstrated that RV positivity represented the higher rate among other viruses (i.e. sapovirus and norovirus) and all other detected viruses had concurrent RV infection [22]. Prevalence of infectious diarrhea influenced by socioeconomic status i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptomatically, the coinfection has a lot of similarity with the mono‐infection but the mixed infections in patients could lead to more severe gastrointestinal symptoms 49 . Interestingly, Abdulazeez et al 54 . has reported no significant association with disease severity.…”
Section: Discussionmentioning
confidence: 99%